2017
DOI: 10.1038/s41598-017-15219-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atomic-level nano-structured hydroxyapatite on adsorption of bone morphogenetic protein-7 and its derived peptide by computer simulation

Abstract: Hydroxyapatite (HA) is the principal inorganic component of bones and teeth and has been widely used as a bone repair material because of its good biocompatibility and bioactivity. Understanding the interactions between proteins and HA is crucial for designing biomaterials for bone regeneration. In this study, we evaluated the effects of atomic-level nano-structured HA (110) surfaces on the adsorption of bone morphogenetic protein-7 (BMP-7) and its derived peptide (KQLNALSVLYFDD) using molecular dynamics and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…For the simulation of the adsorption behavior of the protein, dozens of nanosecond simulations are sometimes appropriate . The root mean square deviation (RMSD) and the interaction energy are usually utilized to assess whether the system is balanced or not, the values of which during the simulation time of 30,000 ps are displayed in Figure . It could be discovered that the whole systems fluctuated slightly at the end of the simulation, which suggested that these systems had reached their equilibrium states.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…For the simulation of the adsorption behavior of the protein, dozens of nanosecond simulations are sometimes appropriate . The root mean square deviation (RMSD) and the interaction energy are usually utilized to assess whether the system is balanced or not, the values of which during the simulation time of 30,000 ps are displayed in Figure . It could be discovered that the whole systems fluctuated slightly at the end of the simulation, which suggested that these systems had reached their equilibrium states.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Δ G calculations suggest that the interaction of CsgB with the HA surface is significantly higher than of CsgA. The strength of those interactions is ruled by interaction distances, as well as the number of interaction sites 41,42 . The higher affinity of CsgB can be due to the stronger interactions of basic amino acids with HA surface, rather than the number of interacting residues.…”
Section: Figure5mentioning
confidence: 97%
“…HA has a high affinity for proteins and other biomolecules 40 . Studies suggest that the pH and mechanical properties of proteins, as well as the surface topology of HA, can affect the protein-HA interactions 41 . Computational studies suggested that -COOand -NH2 are the main interactions sites with HA and play crucial roles in the protein adsorption onto the HA surfaces by forming O-Ca-O connections and hydrogen bonds (H-bonds).…”
Section: Figure5mentioning
confidence: 99%
“…Therefore, thanks to their osteoconductivity property, CaP NPs are ideal delivery systems for BMPs. The interaction mechanism that can occur between BMPs and CaP NPs has been studied by computer simulation, proving that the atomic-level morphology of CaP NPs significantly affects the interaction between proteins and NPs, and that the orientation of BMPs influences their adsorption-desorption behavior [200,201]. The in vitro absorption and release kinetics of BMPs from CaP NPs has been studied showing a sustained release profile of BMPs over 15 days [202].…”
Section: Applications As Nano-carriermentioning
confidence: 99%